L’architecte, l’image et le mot : Le Corbusier dans Cahiers d’art (1926-1933) - Léa Baudat (Les Cahiers de l'École du Louvre)
From 1926 to 1933, Cahiers d’Art, the eclectic magazine edited by Christian Zervos, prominently featured – thanks to the support of the editor and of the architecture columnist, historian Siegfried Giedion – Le Corbusier. The study of this specific case demonstrates how Le Corbusier, beyond his work as a builder, was fully involved in the media of his age. In addition to his activity as an architect, he was a man of letters, journalist, adman and propagandist. How did the architect adapt to the new tools of images and words?